Sport as a business : international, professional and commercial aspects - Dolles, Harald, 1961-; Soderman, Sten. (Houndmills, Basingstoke, Hampshire, UK : Palgrave MacMillan, 2011)
'Sport has a number of distinctive characteristics which impact on the extent of its globalization. This book seeks to gain a deeper understanding of the unique development in sports, its governance, its logic of co-creation of value and the advancement of the industry towards internationalisation, professionalisation and commercialisation.'--
Includes bibliography and index.
Keywords: Sports administration; Sports -- Management; Sports -- Economic aspects; Sports -- International cooperation